İşletmelerde toplam kalite yönetimi - Tepret, Nebahat (My University, 1999)
İşletmelerde Toplam Kalite Yönetimi adı altında bu çalışmanın birinci bölümünde , kalitenin tanımı yapıldıktan sonra,kalitenin sağlanmasında standartlaştırma ve kalite kontrolün önemi üzerinde durulmuş;kalite geliştirme konusunda başlıca yaklaşımları olan ünlü bilim adamalarından;W.Edwards Deming, Joseph M.Juran, Philips B. Crosby'nin kalite yaklaşımları ele alındıktan sonra işletmelerde kalite anlayışı, kalitenin işletmeye ve tüketiciye sağladığı faydalar üzerinde durulmuştur. Kalite, bir ürün veya hizmetin amaca ve isteklere uygun olmasıdır.Başka bir deyişle, ürün veya hizmetin müşteriyi tatmin etmesi, müşteri isteklerini karşılamasıdır.Kalitenin klasik tanımı standartlara uygunluktur. Ancak günümüzde bu tanım yeterli olmamakta. Kalite;müşterilerin ihtiyaçlarına uygunluk olarak tanımlanabilir. İkinci bölümde, günümüzün çağdaş kalite yönetimi olan toplam kalite yönetiminin gelişimi, felsefesi, öğeleri,ilkeleri, toplam kalite yönetiminin özellikleri ve klasik yönetim anlayışıyla toplam kalite yönetimi anlayışının karşılaştırması yapıldı. Toplam Kalite Yönetimi, bir kuruluşun tüm faaliyetlerinde kaliteyi yükseltmeyi hedefler ve böylece her aşamada oluşması söz konusu hataları önler. Tasarım, ürün geliştirme, proses geliştirme, imalat, sevkiyat...hemen her alanda bu tekniklerin bilinçli ve yaygın uygulaması ile gerçekleştirilen çok sayıda iyileştirme projesi ile kuruluş Japon'ların KAİZEN sözcüğü ile ifade ettikleri sürekli gelişmeyi başarmış olur. Bu suretle yüksek kalite, düşük maliyet sonucu elde edilir. Üçüncü bölümde küçük ve orta büyüklükteki işletmeler için iş mükemmelliği modeli ele alınıp çalışanların tatmini anketi uygulanıp değerlendirildi. Çalışanların tatmini anketinin yapılmasındaki amaç; Kuruluşun, çalışanlarının ihtiyaç ve beklentilerini ne ölçüde tatmin ettiğini anlamak,ölçmek ve değerlendirmek (çalışanların; çalışma ortamı, iletişim, kariyer beklentileri, yönetim, değerlendirme, eğitim,tanıma/ taktir v.s.) için yapıldı.

In the first part of the study under the name of Total Quality Management in Foundations the importance of the quality control and standardization of quality was taken into consideration after description of quality. After arguing quality approaches of famous scientists like W. Edwards Deming, Joseph M. Juran, Philips B. Crossby, the importance of the quality for customers and foundations and quality approaches of the foundations was discussed. The quality is suitability of the product or service to proposes and demands. With another express the satisfing of customers from the product or service and it means to meet of customer demands. The classic description of the quality is suitability of the standarts But today this description is not enough to explain the meaning of the quality. Quality can be described the suitability to the customer needs We can shortly describe the quality as suitability to functions and use as Dr. Juran indicated. The foundations are seeing the quality as a strategical means and save and increase the market shares. There fore standardization and quality control take an important place in continuity of quality. The total quality management target to increase the quality in all activities of foundations. By logical and spread application of these techniques in every steps like plan, porduct developing, process developing, production packing and transport improvement project is performed and continous of development as the Japanese expressed KAIZEN has been achieved. As a result of application high quality, lower cast will be obtained. The quality is not limited with product or service, the quality of the complete system as quality of company. It is clear that if the system and employees are qualified, all activities of company have quality. In the second part, the development of total quality management, its elements, its priciples and speciality of total quality management was discussed; classic method and total quality management were compared. The period on satistactory questionnaire for employees; This questionnaire was clone in order to understand, measure and valuation of needs and expectations of employees (working environment, communication, some expectations, method, valuation, education, appicciation) According to the result of the questionnaire, the rate of the general satisfaction on job was 53 %, the rate of the general satisfaction on working and environment conditions was 50 %, the rate of general satisfaction on customer and expectations was 62 %, the rate of general satisfaction on education was 62 %, the rate of general satisfaction on communication and team working was 58 %, the rate of general satisfaction on changes and future was 57 % and in general it was obtained that 62 % of the employees beliexe the results of the questionnaire
Keywords: Toplam Kalite Yönetimi_İşletmeler